Potential impacts of climate change on water resources of Haro River Watershed in Pakistan - Nauman, Saima (2019)
Climate change has resulted in changes in the hydrological fluxes and water distribution across the globe. Pakistan, which is home to almost 200 million people, is a particularly vulnerable country due to poverty, population growth and lack of resources. However, studies quantifying future climate change on water catchment regions in the country are limited due to multiple issues with data and modelling uncertainty. This research aims to quantify projected changes in the climate and its consequent impact on the streamflows of Haro River, the source of water for Khanpur Dam. Firstly, the climate change input is obtained by selecting one out of five downscaled General Circulation Model (GCM) outputs based on the highest coefficient of determination (R2) value from a regression against observed meteorological dataset. The baseline and future meteorological parameters from the selected GCM are then bias corrected using the observed meteorological dataset. For future climate, two Radiative Concentration Pathways (RCP) 4.5 and 8.5 are considered. at two stations, namely Murree (P-1) and Islamabad (P-2). Next, a hydrological model for the basin is developed using the Soil and Water Assessment Tool (SWAT) to integrate the meteorological data and produce simulation of streamflows for the baseline (1976-2005) and future periods (2006-2095). The calibration, validation, uncertainty analysis and the sensitivity analysis of the SWAT Model is conducted in Sequential Uncertainty Fitting 2 (SUFI-2) algorithm. Finally, the change in streamflows is projected through a relative comparison between baseline and future flows on monthly and seasonal scale. The study found that the maximum (minimum) temperature at P-1 is expected to increase by 3.1°C (3.2°C) under RCP 4.5 and 4.0°C (4.3°C) under RCP 8.5 in the future. Precipitation is expected to rise from 8.9% under RCP 4.5 to 14.3% under RCP 8.5. Similarly, at P-2, the maximum (minimum) temperature is anticipated to increase by 3.3°C (3.3°C) under RCP 4.5 and 4.1°C (4.2°C) under RCP 8.5. Precipitation is projected to increase between 15.4% (RCP 4.5) and 23.1% (RCP 8.5) compared to the baseline scenario. SWAT produced good model performance with Nash Sutcliffe Efficiency (NSE) and R2 values of 0.80 (0.77) and 0.82 (0.77) respectively during the calibration (validation) period. Simulation of baseline and future streamflows using the calibrated SWAT indicates an increase from average annual baseline streamflows of 7.7 m3/s to 8.7 m3/s (9.3 m3/s) under RCP 4.5 (RCP 8.5). Maximum streamflows expected during the month of July, are projected to increase from baseline streamflow of 21.3 m3/s to 28.2 m3/s (32.6 m3/s) under RCP 4.5 (RCP 8.5). In summer season, compared to baseline streamflows of 13.1 m3/s, the streamflows are expected to be 4.2 m3/s (6.8 m3/s) higher under RCP 4.5 (RCP 8.5). This study will help the policy makers in conceiving prudent schemes for effective utilization of water supply throughout the year. The new policies may focus on increasing water storage capacity of the dam reservoir in the future resulting from projected increase in streamflows.